Regulation of glycolysis-derived L-lactate production in astrocytes rescues the memory deficits and Aβ burden in early Alzheimer's disease models - Xiu Yang; Yuan-Hao Chen; Le Liu; Zheng Gu; Yue You; Jing-Ru Hao; Nan Sun; Can Gao (Elsevier, 2024)
Aberrant energy metabolism in the brain is a common pathological feature in the preclinical Alzheimer's Disease (AD). Recent studies have reported the early elevations of glycolysis-involved enzymes in AD brain and cerebrospinal fluid according to a large-scale proteomic analysis. It's well-known that astrocytes exhibit strong glycolytic metabolic ability and play a key role in the regulation of brain homeostasis. However, its relationship with glycolytic changes and cognitive deficits in early AD patients is unclear. Here, we investigated the mechanisms by which astrocyte glycolysis is involved in early AD and its potential as a therapeutic target. Our results suggest that Aβ-activated microglia can induce glycolytic-enhanced astrocytes in vitro, and that these processes are dependent on the activation of the AKT-mTOR-HIF-1α pathway. In early AD models, the increase in L-lactate produced by enhanced glycolysis of astrocytes leads to spatial cognitive impairment by disrupting synaptic plasticity and accelerating Aβ aggregation. Furthermore, we find rapamycin, the mTOR inhibitor, can rescue the impaired spatial memory and Aβ burden by inhibiting the glycolysis-derived L-lactate in the early AD models. In conclusion, we highlight that astrocytic glycolysis plays a critical role in the early onset of AD and that the modulation of glycolysis-derived L-lactate by rapamycin provides a new strategy for the treatment of AD.